Medical and psychological outcomes for young adults with Type 1 diabetes: no improvement despite recent advances in diabetes care. Issue 2 (19th September 2013) - Johnson, B.; Elliott, J.; Scott, A.; Heller, S.; Eiser, C.
Abstract Aim To assess medical and psychological outcomes among young people with Type 1 diabetes and to compare medical outcomes with a previous audit. Methods An observational study in two diabetes clinics for young adults (aged 16–21 years) in Sheffield, UK. Young people (n = 96: 81.4% response rate) with Type 1 diabetes (diagnosed > 6 months) completed measures of depressive symptoms, anxiety and disordered eating and consented for their medical records to be consulted. Results Mean HbA1c (86 ± 23 mmol/mol; 10.0 ± 2.1%); was comparable with that reported previously and considerably higher than recommended (< 58 mmol/mol or 7.5%). Screening rates were improved and non‐attendance was lower than previously reported, but levels of non‐proliferative retinopathy have increased. Microvascular complications are present in 46.9% of those diagnosed more than 7 years. Elevated levels of disordered eating were reported by 35.1%. Those scoring above cut‐off levels for clinical anxiety (26.6%) and depression (10.9%) are comparable with other work with young people with Type 1 diabetes. Conclusions Despite technological advances and improvements to delivery of care, HbA1c remain above recommended levels in a significant proportion of young people, many of whom already have microvascular complications. We need to learn from European centres who achieve better results, improve transition from paediatric care, integrate mental health support with diabetes care provision and take into account young people's views about clinic.